2017
DOI: 10.1002/2211-5463.12212
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the essential biotin‐dependent carboxylase AccA3 from Mycobacterium tuberculosis

Abstract: Biotin‐dependent acetyl‐CoA carboxylases catalyze the committed step in type II fatty acid biosynthesis, the main route for production of membrane phospholipids in bacteria, and are considered a key target for antibacterial drug discovery. Here we describe the first structure of AccA3, an essential component of the acetyl‐CoA carboxylase system in Mycobacterium tuberculosis (MTb). The structure, sequence comparisons, and modeling of ligand‐bound states reveal that the ATP cosubstrate‐binding site shows distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
(97 reference statements)
0
6
0
Order By: Relevance
“…ACC is also essential for growth of M. tuberculosis , and thus represents a potential target for anti‐tuberculous drugs [33,35] . We demonstrate here for the first time anti‐tubercular activities of moiramide derivatives, however on an intermediate level compared to isoniazid (MIC 0.429 μg/mL).…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…ACC is also essential for growth of M. tuberculosis , and thus represents a potential target for anti‐tuberculous drugs [33,35] . We demonstrate here for the first time anti‐tubercular activities of moiramide derivatives, however on an intermediate level compared to isoniazid (MIC 0.429 μg/mL).…”
Section: Resultsmentioning
confidence: 71%
“…ACC is also essential for growth of M. tuberculosis, and thus represents a potential target for anti-tuberculous drugs. [33,35] We demonstrate here for the first time anti-tubercular activities of moiramide derivatives, however on an intermediate level compared to isoniazid (MIC 0.429 μg/mL). While moiramide B was inactive at 25 μg/mL, the more stable cinnamoyl derivatives 22 and biarylether 21 exhibited the lowest MIC (9.9 and 9.2 μg/ mL) for Mtb and thus represent interesting starting points for further optimization.…”
Section: Chemmedchemmentioning
confidence: 74%
See 1 more Smart Citation
“…In addition, BC1 contained 46.2% and 43.9% sequence identities with M. tuberculosis and S. coelicolor ACC α-subunit ( Fig. S1B ), which both contain a fused BC and BCCP domains for dual functionality ( 25 ). These observations suggested that C. aurantiacus BC1 most likely has a BCCP domain (Ala459-Lys596) fused to its BC domain (Met1-Glu452).…”
Section: Resultsmentioning
confidence: 99%
“…In organisms such as Streptomyces coelicolor and Mycobacterium tuberculosis , the BC and BCCP are fused, called α subunit. However, the crystal structure of M. tuberculosis α-subunit (AccA3) only revealed a dimer of the ATP-bound BC domain, the BCCP was unresolved in the structure ( 25 ). Although the crystal structure of the recombinant E. coli BCCP-BC complex revealed a tetramer of two BC homodimers clamped by four BCCP molecules ( 16 ), the stoichiometry, structural, and functional correlations between the BC and BCCP subunits of the heteromeric ACCs remain controversial.…”
Section: Introductionmentioning
confidence: 99%